Using community website as an informal learning environment among Malaysian pharmacy students - Al-lela, Omer Qutaiba; Elkalmi, Ramadan Mohamed Mahmod; Alkoudmani, Ramez M.; Awadh, Ammar Ihsan Jawad; Jamshed, Shazia Qasim; Al-Shami, Abdul Kareem (Science and Education Publishing, 2015)
Objective: This study was conducted to analyse students’ insight on informal learning by means of social networks and community websites. Methods: Survey forms were distributed to all 360 students of Kulliyyah of Pharmacy of IIUM. Data analysis has been done using IBM SPSS software 20, and descriptive statistics were used to study the demographic characteristics of the students in relation to their use of social networking sites (SNSs). Results: 240 students were answered. The results revealed that the highest rating with mean (SD) = 4.53 (0.63) were related to accessing course notes and other teaching materials. Most students agreed that SNSs were helpful to their courses, mean (SD) = 4.18 (0.73). Conclusion: The findings of the study indicate that pharmacy students at IIUM use SNSs and other community websites as tools for academic purposes.